The night-time sleep and autonomic activity of male and female professional road cyclists competing in the Tour de France and Tour de France Femmes - Sargent, C.; Jasinski, S.; Capodilupo, E. R.; Powers, J.; Miller, D. J.; Roach, G. D. (Sports Medicine - Open, 2024)
Background Sleep is a critical component of recovery, but it can be disrupted following prolonged endurance exercise. The objective of this study was to examine the capacity of male and female professional cyclists to recover between daily race stages while competing in the 2022 Tour de France and the 2022 Tour de France Femmes, respectively. The 17 participating cyclists (8 males from a single team and 9 females from two teams) wore a fitness tracker (WHOOP 4.0) to capture recovery metrics related to night-time sleep and autonomic activity for the entirety of the events and for 7 days of baseline before the events. The primary analyses tested for a main effect of `stage classification`—i.e., rest, flat, hilly, mountain or time trial for males and flat, hilly or mountain for females—on the various recovery metrics.